Selective Serotonin Reuptake Inhibitor Pharmacokinetics During Pregnancy: Clinical and Research Implications - Poweleit, Ethan A.; Cinibulk, Margaret A.; Novotny, Sarah A.; Wagner-Schuman, Melissa; Ramsey, Laura B.; Strawn, Jeffrey R. (Frontiers in Pharmacology, 2022)
Pregnancy and associated physiologic changes affect the pharmacokinetics of many medications, including selective serotonin reuptake inhibitors—the first-line pharmacologic interventions for depressive and anxiety disorders. During pregnancy, SSRIs exhibit extensive pharmacokinetic variability that may influence their tolerability and efficacy. Specifically, compared to non-pregnant women, the activity of cytochrome P450 (CYP) enzymes that metabolize SSRIs drastically changes, (e.g., decreased CYP2C19 activity and increased CYP2D6 activity). This perspective examines the impact of pharmacokinetic genes—related to CYP activity on SSRI pharmacokinetics during pregnancy. Through a simulation-based approach, plasma concentrations for SSRIs metabolized primarily by CYP2C19 (e.g. escitalopram) and CYP2D6 (e.g. fluoxetine) are examined and the implications for dosing and future research are discussed.